Talent Management: An integrative review of theoretical and industrial practices / Raja Iskandar Putera Raja Mustapha ... [et al.] - Raja Mustapha, Raja Iskandar Putera Raja Mustapha; Mohd Zool Fadli Ibrahim, Mohd Zool Fadli Ibrahim; Mohamad Saber, Joesri; Salim, Azlan (Universiti Teknologi MARA Selangor, 2019)
Although the term Talent Management (TM) has been around for a long time, the application of the theoretical findings in the very field is still lacking. This phenomenon is also prevalent in the hospitality industry where – although it seems counter-intuitive as the hospitality industry is a people-driven industry – the employees are just regarded as just another person on the payroll hired to do a task or a job and not a person or a commodity with ability that could be nurtured also enhanced for the betterment of the organisation. One of the most common issues faced by the hospitality industry is that of employee retention hence it is pertinent that “talent” is handled or managed systematically and with a more calculated thought process. This paper is therefore written with the idea of bridging that gap of knowledge found between the theoretical application and industrial application thus further elaborating the concept of TM through an integrative review process.